One-pot synthesis of thiazino[2, 3, 4-hi]indole derivatives through a tandem oxidative coupling/heteroannulation process. Issue 34 (12th April 2017) - Mao, Xi; Tong, Tao; Fan, Senbao; Fang, Liting; Wu, Jingyi; Wang, Xiaoxia; Kang, Honglan; Lv, Xin
Abstract : A novel and expedient one-pot synthesis of thiazino[2, 3, 4- hi ]indole derivatives was developed through a tandem oxidative coupling/heteroannulation process. Abstract : A novel and expedient one-pot synthesis of thiazino[2, 3, 4- hi ]indole derivatives from o -haloaryl enamines and o -bromothiophenols has been developed. The tandem oxidative coupling/heteroannulation reactions exhibit high selectivity and good efficiency. The polycyclic heterocyclic products obtained might be useful in medicinal chemistry and materials science.